The osteoarthritis bone score (OABS): a new histological scoring system for the characterisation of bone marrow lesions in osteoarthritis. Issue 5 (May 2022) - Koushesh, S.; Shahtaheri, S.M.; McWilliams, D.F.; Walsh, D.A.; Sheppard, M.N.; Westaby, J.; Haybatollahi, S.M.; Howe, F.A.; Sofat, N.
Summary: Objectives: Bone marrow lesions (BMLs) are associated with pain in osteoarthritis (OA), but histological scores for OA focus on cartilage pathology. We developed a new scoring system, the Osteoarthritis Bone Score (OABS), to characterise OA-related BMLs. Methods: BML/non-BML tissues identified by Magnetic Resonance Imaging (MRI) in 10 knee OA subjects were harvested at total knee replacement (TKR). Osteochondral tissue from a further 140 TKR and 23 post-mortem (PM) cases was assessed. Histological features distinguishing MRI-defined BML/non-BML tissues on qualitative analysis were classified as present (0) or absent (1), summated for the OABS, validated by Rasch analysis and sensitivity to distinguish between sample groups. Immunohistochemistry for PGP9.5 assessed innervation. Results: Subchondral characteristics associated with BML tissues were cysts, fibrosis, hypervascularity, cartilage islands, trabecular thickening, loss of tidemark integrity and inflammatory cell infiltration. PGP9.5 immunoreactive perivascular nerves were associated with BMLs. OABS performed well as a measurement tool, displayed good reliability (Cronbach alpha = 0.68), had a 2-factor structure (trabecular/non-trabecular), with moderate correlation between the two factors ( r = 0.56, 95% CI 0.46, 0.65). OABS scores were higher in TKR than PM cases with chondropathy, median difference 1.5 (95% CI -2, 0). OABS and Mankin scores similarly distinguished TKR from non-OA controls, but only OABS was higher in BML than non-BML tissues, median difference −4 (95% CI -5 to −2). Conclusions: OABS identifies and validly quantifies histopathological changes associated with OA BMLs. Histopathology underlying BMLs may represent 2 inter-related pathological processes affecting trabecular/non-trabecular structures. Increased vascularity/perivascular innervation in BMLs might contribute to pain.